2011
DOI: 10.1007/s12564-011-9145-1
|View full text |Cite
|
Sign up to set email alerts
|

‘One assessment doesn’t serve all the purposes’ or does it? New Zealand teachers describe assessment and feedback

Abstract: Within the Asia-Pacific community, the New Zealand Ministry of Education has been one of few educational authorities to adopt an Assessment for Learning (AfL) framework and actively promote formative uses of assessment. This paper reports the results of a qualitative study in which eleven New Zealand secondary teachers in two focus groups discussed their conceptions of assessment and feedback. These data were examined to see how teachers defined and understood assessment and feedback processes to identify how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
0
26
1
4
Order By: Relevance
“…The Commonalities and Dissonances Between High-School Students' and Their Science Teachers' Conceptions of Science Learning and Conceptions of Science Assessment: A Taiwanese sample study Introduction Researchers have been striving to identify individuals' educational conceptions such as students' and teachers' conceptions of learning and of assessment (Chan, 2011;Eren, 2010;Gijbels & Dochy, 2006;Irving, Harris, & Peterson, 2011). In general, conceptions of learning represent an individual view or perception about learning objectives and process, whereas conceptions of assessment refer to how and what he/she conceive of as assessment activities in the learning environment (Benson & Lor, 1999;Peterson & Irving, 2008).…”
Section: The Commonalities and Dissonances Between High-school Studenmentioning
confidence: 99%
“…The Commonalities and Dissonances Between High-School Students' and Their Science Teachers' Conceptions of Science Learning and Conceptions of Science Assessment: A Taiwanese sample study Introduction Researchers have been striving to identify individuals' educational conceptions such as students' and teachers' conceptions of learning and of assessment (Chan, 2011;Eren, 2010;Gijbels & Dochy, 2006;Irving, Harris, & Peterson, 2011). In general, conceptions of learning represent an individual view or perception about learning objectives and process, whereas conceptions of assessment refer to how and what he/she conceive of as assessment activities in the learning environment (Benson & Lor, 1999;Peterson & Irving, 2008).…”
Section: The Commonalities and Dissonances Between High-school Studenmentioning
confidence: 99%
“…Andra studier anknyter läraruppfattningar till implementeringar av Bedömning för Lärande (BfL) och sammanfattningsvis kan konstateras att även dessa studier urskiljer såväl formativa som summativa mål med återkoppling (Gamlem, 2015;Irving, Harris & Peterson, 2011;Brown, Harris & Harnett, 2012). Gamlem (2015) genomförde intervjuer med tre lärare inför en implementering av Bedömning för Lärande i en norsk högstadieskola.…”
Section: Mål Med åTerkopplingunclassified
“…Understanding and explaining feedforward has been enabled through a series of studies on feedback that focused on presenting the concept (Hattie & Timperley, 2007;Higgins, Hartley, & Skelton, 2001;Lyster & Ranta, 1997), its importance during learning (Brown, 2004;Brown, Harris, & Harnett, 2012;Clarke, 2003;Hattie & Timperley, 2007;Pajares & Graham, 1998), the receiver (Higgins et al, 2001;Irving, Harris, & Peterson, 2011;Wiggins, 2004), the feedback source (Brown et al, 2012;Peterson & Irving, 2008;Topping, 2010), administration conditions (Brown et al, 2012;Hattie & Timperley, 2007), the moment of giving feedback (Hattie & Timperley, 2007), the methods of giving it (Koen et al, 2012), typology (Fink, 2007; Harris, Brown, & Harnett, 2014;Hattie & Timperley, 2007;Irving et al, 2011;Mori, 2011;Murtagh & Baker, 2009;Shute, 2008), its impact (Brown, 2004;Gibbs & Simpson, 2004;Koen et al, 2012), and its efficiency (Akalin & Sucuoglu, 2015;Hattie & Timperley, 2007;Irving et al, 2011;Shute, 2008;Topping, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Their questions were proof that students did not have the competence to elaborate sketch maps, that they had deficiencies related to the map components, and that they needed the professor as a source of specific information about their performances, thus confirming Pajares and Graham's (1998) assertions. Student feedback occurred: in the moment; upon request (Hattie & Timperley, 2007), it was clarifying, direct, spoken and individual; negative (Murtagh & Baker, 2009); corrective (Mori, 2011), because it indicated that the task text was not complete enough for the students to understand the task itself; and also positive, as students had asked for information because they were motivated to solve the task (Irving et al, 2011) and because the questions' tone and content did not disturb the initial positive learning environment (Koen et al, 2012). Peer and student feedback was confirmed to be no less reliable or valid than professor feedback (Topping, 2010).…”
Section: Sr 1: Receiving the Task The Feedforward And Studying The Mmentioning
confidence: 99%